PENGARUH FINANCIAL KNOWLEDGE DAN FINANCIAL MANAGEMENT BEHAVIOR TERHADAP KEBERLANJUTAN USAHA - Pattireuw, Avilia Martha; Janwarin, Xaverius M; Tomasoa, Theodora F (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2025)
This study aims to analyze the influence of financial knowledge and financial management behavior on business sustainability. The method in this study uses a quantitative approach. The population in this study were owners or business actors of grocery stores located in Suli Village, Salahutu District. The sample determination used was the Purposive Sampling technique using the likert scale technique. Data was collected by disributing questionnaires as 50 respondents. By using statistical analysis parameters, namely validity test, reliability test, multicorrelation test, heteroscedasticity test, multiple linear analysis, determonation coefficient analysis, partial test and simultaneous test. Based on the results of the SPSS data processing analysis, it shows that the partial test shows that the financial knowledge variable has a positive and significant influence on business sustainability, while the financial management behavior variable has no influence on business sustainability, and the simultaneous test shows that the financial knowledge and financial management behavior variables have a positive and significant influence on business sustainability.